The Relationship between Organizational Justice And Trust To Organizational Commitment Of The Nursing Staff - داؤد, نسرين اسكندر; اصبيره, ولاء هاشم; حلوم, زينب أديب (Latakia University Journal -Medical Sciences Series, 2021)
The study aimed to determine the relationship of organizational justice and organizational confidence with the organizational commitment of the nursing staff at Tishreen University Hospital in Lattakia City, as well as to determine the level of organizational justice, and of organizational confidence, and of organizational commitment of the nursing body at Tishreen University Hospital. The sample consisted of (200) nurses working at Tishreen University Hospital, who were present during the data collection period (convenience sample). The researcher used a questionnaire to assess the organizational justice That was used by the researcher Alian (2016) in his study on organizational justice, and a questionnaire to assess organizational confidence, where the scale used by the researcher Khwain (2015) on the organizational confidence , and to assess the organizational commitment, the scale used by Salman (2013) in his assess of the Organizational commitment, to collect data related to the study, and after the data were unpacking, it was statistically processed and tabulated using the statistical program SPSS version (20). The most important results of the study: that the level of organizational justice of the nursing staff as a whole was weak, and the level of organizational confidence and the level of organizational commitment of the nursing staff as a whole was average, and it was also found that there is no statistically significant relationship between organizational justice and organizational commitment, and that there is a strong and statistically significant relationship between organizational confidence and organizational commitment.